PERAN ANALISIS SUARA DALAM DETEKSI DINI KOGNITIF PADA LANSIA: STUDI PENDAHULUAN - Kristian, Kevin; Adhitya, Paskalis; Tirta Wening, Andrea; Indrawan, Novelya; Indrajaya, Feryandinata; Yauw, Michael (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2025)
ABSTRACT Introduction: The increase in life expectancy makes the cognitive abilities of the elderly important. The need for a rapid diagnosis of cognitive impairment renders the currently available instruments inadequate. Standardization of the use of voice analysis for cognitive assessment is required for quick diagnosis. Aim: To determine the relationship between voice components and cognitive impairment in the elderly. Methods: A descriptive and analytical cross-sectional study was conducted on elderly individuals over 60 years old who did not have visual or hearing impairments. Cognitive assessment using MoCA-INA was performed on 107 elderly individuals who met the inclusion criteria and were categorized into normal and cognitively impaired groups. Results: The majority of the study respondents were aged 61-70 years (57.9%), not frail (93.5%), had multimorbidity (60.74%), had a habit of exercising (66.4%), and had a formant frequency 1 (F1) of the vowel /e/ <500.9 Hz (50.5%). Univariate analysis showed that F1 of the vowel /e/ had very high variability (107041.294), and the compare means analysis showed a significant relationship (p=0.034). Discussion: Most of the elderly in this study did not have cognitive impairment. There was a relationship between F1 of the vowel /e/ and cognitive impairment at a MoCA-INA cut-off score of 22. There was no relationship between age, exercise habits, multimorbidity, fundamental frequency of the vowels /a/ and /e/, amplitude of the vowels /a/ and /e/, F1 and F2 of the vowel /a/, and F2 of the vowel /e/. Keywords: cognitive impairment, elderly, formant 1 (F1), voice analysis